PARAQUAT AND OTHER DESSICANT AND BLEACHING HERBICIDES – THEIR INFLUENCE ON WEEDS, CROP PLANTS AND HUMAN AND ANIMAL HEALTH - Nikolić, Bogdan R; Sanja, Sanja; Pisinov, Boris; Jovanović, Vladan; Dudić, Tijana; Dugalić, Miloš (Acta herbologica, 2024)
The paper provides an overview of various aspects of desiccants and bleaching herbicides, from various chemical groups, which have in common the drying and bleaching of leaf mass. In weed plants, they can act as total or selective herbicides, and applied in the mature stages of the crop, by drying the leaf mass, they promote the maturation of some important crops (sunflower, soybeans, potatoes). More or less, all these various herbicides are highly or significantly toxic, which greatly complicates their application. In the EU, there was an initiative to ban some of them (eg Paraquat). However, we are of the opinion that despite their significant toxicity, they should be considered as an alternative to some other herbicides.